Polyurethane-based thermal interface materials including silane-terminated urethane prepolymers

The thermal interface material composition, featuring a non-reactive polyurethane prepolymer, aluminum trihydroxide, silane-terminated urethane prepolymer, and plasticizer, solves the slipping problem in battery-powered vehicles, achieving effective heat management with improved adhesion and thermal conductivity.

JP7648637B2Active Publication Date: 2025-03-18DDP SPECIALTY ELECTRONICS MATERIALS US LLC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022544342
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-03
Filing Date
2021-01-12
Publication Date
2025-03-18
Estimated Expiration
2041-01-12

AI Technical Summary

Technical Problem

Current thermal interface materials (TIMs) used in battery-powered vehicles, particularly those with high thermal conductivity fillers like aluminum trihydroxide (ATH), tend to slip when placed in a vertical position under climatic conditions, leading to ineffective heat management.

Method used

A thermal interface material composition comprising a non-reactive polyurethane prepolymer, 70-95% aluminum trihydroxide, 0.15-1.5% silane-terminated urethane prepolymer, and 1-20% plasticizer, which improves adhesion and prevents slipping while maintaining high thermal conductivity.

Benefits of technology

The proposed TIM composition effectively addresses the slipping issue, ensuring reliable heat management in battery-powered vehicles by enhancing adhesion and maintaining high thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648637000001
    Figure 0007648637000001
  • Figure 0007648637000002
    Figure 0007648637000002
Patent Text Reader

Abstract

Disclosed herein is a thermal interface material (TIM) composition comprising: a) a non-reactive polyurethane prepolymer; b) about 70-95 wt% aluminum trihydroxide (ATH); c) about 0.15-1.5 wt% of at least one silane-terminated urethane prepolymer; and d) about 1-20 wt% of at least one plasticizer, where the total weight of the thermal interface material adds up to 100 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to thermal interface materials and their use in battery powered vehicles. [Background technology]

[0002] Compared to traditional modes of transportation, battery-powered vehicles offer important advantages such as light weight, reduced CO2 emissions, etc. However, many technical challenges still need to be overcome to ensure optimal utilization of this technology. For example, one current effort in the industry is to increase the driving range of battery-powered vehicles by developing higher density batteries. This also leads to the need to develop better thermal management systems for high density batteries. Summary of the Invention [Problem to be solved by the invention]

[0003] In battery-powered vehicles, the battery cells or modules are thermally connected to the cooling unit by thermal interface materials (TIMs). Such TIMs are typically formed from polymer-based materials filled with thermally conductive fillers. To achieve thermal conductivities of 2 W / m·K or more, fillers with thermal conductivities of 100 W / m·K or more, such as boron nitride or aluminum powder, can be used. However, such fillers are expensive and abrasive. A cheaper and non-abrasive alternative is aluminum trihydroxide (ATH), and it has been demonstrated that with a polyurethane-based TIM with a high loading of ATH, it is achievable to obtain a TIM with high thermal conductivity and low viscosity. However, it has been found that such a TIM has a tendency to slip when placed in a vertical position under climatic conditions. Therefore, improvements are still needed to solve this slippage problem. [Means for solving the problem]

[0004] Provided herein is a thermal interface material composition comprising, adding up to 100 wt% of the total weight of the thermal interface material, a) a non-reactive polyurethane prepolymer that is i) the reaction product of at least one polyisocyanate and at least one hydroxy group-containing compound, and ii) is substantially free of residual isocyanate groups; b) about 70-95 wt% aluminum trihydroxide; c) about 0.15-1.5 wt% of at least one silane-terminated urethane prepolymer; and d) about 1-20 wt% of at least one plasticizer.

[0005] In one embodiment of the thermal interface material composition, the non-reactive polyurethane prepolymer is present at a level of about 1-25 weight percent, based on the total weight of the composition.

[0006] In a further embodiment of the thermal interface material composition, the silane-terminated urethane prepolymer is present at a level of about 0.15 to 1.2 weight percent, based on the total weight of the composition.

[0007] In yet a further embodiment of the thermal interface material composition, the silane-terminated urethane prepolymer is present at a level of about 0.2 to 0.8 weight percent, based on the total weight of the composition.

[0008] In yet further embodiments of the thermal interface material composition, the silane-terminated urethane prepolymer is selected from the reaction product of at least one isocyanate-functionalized silane with one or more polyols, the reaction product of at least one isocyanate-functionalized silane with one or more hydroxyl-terminated prepolymers, and the reaction product of at least one nucleophile-functionalized silane with one or more isocyanate-terminated prepolymers.

[0009] In yet a further embodiment of the thermal interface material composition, the silane-terminated urethane prepolymer has a molecular weight in the range of about 200-5000.

[0010] In yet a further embodiment of the thermal interface material composition, the silane-terminated urethane prepolymer has a molecular weight in the range of about 300-3000.

[0011] In yet a further embodiment of the thermal interface material composition, the silane-terminated urethane prepolymer has a molecular weight in the range of about 500-2000.

[0012] Further provided herein is an article comprising the thermal interface material composition provided above.

[0013] In one embodiment of the article, the article further includes a battery module formed from one or more battery cells and a cooling unit, the battery module being connected to the cooling unit via the thermal interface material composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Disclosed herein is a thermal interface material (TIM) composition comprising: a) a non-reactive polyurethane prepolymer; b) about 70-95 wt% aluminum trihydroxide (ATH); c) about 0.15-1.5 wt% of at least one silane-terminated urethane prepolymer; and d) about 1-20 wt% of at least one plasticizer, the total weight of the thermal interface material adding up to 100 wt%.

[0015] In accordance with the present disclosure, the non-reactive polyurethane prepolymer used herein is the reaction product of at least one polyisocyanate and at least one hydroxyl-containing compound.In addition, the non-reactive polyurethane prepolymer used herein is substantially free of residual isocyanate groups, i.e., there is less than about 0.8% by weight or less than about 0.4% by weight of residual isocyanate groups in the prepolymer.

[0016] In accordance with the present disclosure, the polyisocyanates used herein are multifunctional isocyanates (e.g., diisocyanates and triisocyanates) and may be aliphatic, cycloaliphatic or aromatic polyisocyanates. Exemplary multifunctional isocyanates used herein include, without limitation, ethylene diisocyanate; hexamethylene-1,6-diisocyanate (HDI); isophorone diisocyanate (IPDI); 4,4'-, 2,2'- and 2,4'-dicyclohexylmethane diisocyanate (HDI); 12 MDI; norbornene diisocyanate; 1,3- and 1,4-(bisisocyanatomethyl)cyclohexane (including its cis- and trans-isomers); tetramethylene-1,4-diisocyanate (TMXDI); 1,12-dodecane diisocyanate; 2,2,4-trimethylhexamethylene diisocyanate; 2,2'-, 2,4'- and 4,4'-methylenediphenyl diisocyanate (MDI); carbodiimide modified MDI; 2,4- and 2,6-toluene diisocyanate (TDI); 1,3- and 1,4-phenylene diisocyanate; 1,5-naphthylene diisocyanate; triphenylmethane-4,4',4" -triisocyanate; polyphenylpolymethylene polyisocyanate, etc. In one embodiment, the polyisocyanate used herein is an aliphatic polyisocyanate. In a further embodiment, the polyisocyanate used herein is selected from hexamethylene-1,6-diisocyanate; isophorone diisocyanate; 1,3-(bisisocyanatomethyl)cyclohexane; 1,4-(bisisocyanatomethyl)cyclohexane; or a mixture of two or more thereof. In yet a further embodiment, the polyisocyanate used herein is hexamethylene-1,6-diisocyanate.

[0017] The polyisocyanates may have a percent NCO content of about 10-60%. In certain embodiments, the polyisocyanates used herein may have an average isocyanate functionality of at least about 2, or at least about 2.2, or at least about 2.4; and about 4 or less, or about 3.5 or less, or about 3 or less. In further embodiments, the equivalent weight of the polyisocyanates may be at least about 100, or at least about 110, or at least about 120; and about 300 or less, or about 250 or less, or about 200 or less.

[0018] The hydroxyl group-containing compound used herein may contain one or more hydroxyl groups, such as monols, diols, triols, or polyols. Exemplary hydroxyl group-containing compounds include, without limitation, polyether polyols, polyester polyols, polycarbonate polyols, alcohols, and the like. In one embodiment, the hydroxyl group-containing compound is a polyether containing one or more terminal hydroxyl groups, i.e., a polyether polyol. Exemplary polyether polyols used herein include, without limitation, i) monols or fatty acid-based alcohols, such as alkoxylated alcohols (alkoxylating agents are ethylene oxide, propylene oxide, or butylene oxide, and starting alcohols are methanol, ethanol, butanol, or longer fatty alcohols); ii) diols, such as 1,4-butanediol; iii) polyether polyols based on polyethylene oxide, polypropylene oxide, or polybutylene oxide, and the like. The hydroxyl-containing compounds used herein may have a functionality of about 1-7, or about 1-5, or about 1-3, or about 1-2, and a molecular weight of about 90-5000, or about 90-3000, or about 90-2000.

[0019] Along with the polyisocyanate and the hydroxyl group-containing compound, additional additives may also be added when preparing the non-reactive polyurethane prepolymer. These include catalysts, chain extenders, crosslinkers, fillers, moisture scavengers, colorants, etc. In particular, a number of aliphatic and aromatic amines (e.g., diaminobicyclooctane, 1,4-diazabicyclo[2.2.2]octane (DABCO, etc.)), organometallic compounds (e.g., dibutyltin dilaurate (DBTDL), dibutyltin diacetate), alkali metal salts of carboxylic acids and phenols (calcium, magnesium, strontium, barium, salts of hexanoic acid, octanoic acid, naphthenic acid, linolenic acid) may be used as catalysts.

[0020] In addition, to obtain a non-reactive polyurethane prepolymer substantially free of residual isocyanate groups, a stoichiometric or excess stoichiometric amount of a hydroxyl-containing compound must be used in the reaction, i.e., the ratio of -OH groups in the hydroxyl-containing compound to -NCO groups in the polyisocyanate is equal to or greater than 1. The preparation of the non-reactive polyurethane prepolymer includes mixing together at least one polyisocyanate, at least one hydroxyl-containing compound, and other additives such as a catalyst; stirring the reaction mixture at about 20-80° C. for about 10-60 minutes under nitrogen or vacuum; cooling the reaction product to room temperature; and storing the reaction product in a sealed container.

[0021] The non-reactive polyurethane prepolymers used herein may have a molecular weight ranging from about 2,000 to 50,000 g / mol, or from about 3,000 to 30,000 g / mol, or from about 4,000 to 15,000 g / mol.

[0022] In accordance with the present disclosure, the non-reactive polyurethane prepolymer may be included in the TIM composition at a level of about 1-25 wt%, or about 2-20 wt%, or about 5-15 wt%, based on the total weight of the composition.

[0023] The ATH used herein can be a unimodal ATH powder or an ATH powder having a multimodal particle size distribution (e.g., bimodal, trimodal, etc.). When a unimodal ATH powder is used, the average particle size can be in the range of about 5 to 100 μm. Also, when a multimodal ATH powder is used, the average particle size of the smallest particles can be less than about 10 μm, while the average particle size of the largest particles can be greater than about 50 μm. In addition, the ATH powder used herein can also be surface treated with silanes, titanates, carboxylates, and the like.

[0024] In accordance with the present disclosure, ATH powder may be included in the composition at a level of about 70-95% by weight, or about 75-90% by weight, or about 80-85% by weight.

[0025] Silane-terminated urethane prepolymers are urethane prepolymers in which some or all of the isocyanate groups are end-capped with an organosilane. Silane-terminated urethane prepolymers can be prepared by reacting at least one isocyanate-functionalized silane with one or more polyols, or by reacting at least one isocyanate-functionalized silane with one or more hydroxyl-terminated prepolymers, or by reacting at least one nucleophile-functionalized silane (e.g., aminosilane, mercaptosilane, etc.) with one or more isocyanate-terminated prepolymers. The prepolymers can be selected from the group consisting of polyurethanes, polyureas, polyethers, polyesters, poly(meth)acrylates, polycarbonates, polystyrenes, polyamines or polyamides, polyvinyl esters, styrene / butadiene copolymers, polyolefins, polysiloxanes, and polysiloxane-urea / urethane copolymers. The silane-terminated urethane prepolymers used herein may have a molecular weight ranging from about 200 to 5000, or from about 300 to 3000, or from about 500 to 2000.

[0026] Suitable silane-terminated urethane prepolymers may be any of those disclosed in EP 1924621 and U.S. Pat. Nos. 3,933,756; 5,756,751; 6,288,198; 6,545,087; 6,703,453; 6,809,170; 6,833,423; 6,844,413; 887,964; 6,998,459; 7,115,696; 7,465,778; 7,060,750; and 7,309,753, which are incorporated herein by reference. Suitable silane-terminated urethane prepolymers are also commercially available. For example, they are available under the trade name Desmoseal TM from Covestro or under the trade name MS Polymer TM or from Momentive under the trade name SPUR+*.

[0027] In accordance with the present disclosure, at least one silane-terminated urethane prepolymer may be included in the TIM composition at a level of about 0.15-1.5 wt%, or about 0.15-1.2 wt%, or about 0.2-0.8 wt%, based on the total weight of the composition.

[0028] The TIM compositions disclosed herein further comprise about 1-20 wt%, or about 2-15 wt%, or about 3-10 wt%, of at least one plasticizer, based on the total weight of the composition. Plasticizers are well known in the art, and it is within the ability of one of ordinary skill in the art to select a suitable plasticizer according to parameters such as compatibility and desired properties (e.g., viscosity) of the final composition.

[0029] In general, suitable plasticizers include ester derivatives of acids and anhydrides such as adipic acid, azelaic acid, benzoic acid, citric acid, dimer acid, fumaric acid, isobutyric acid, isophthalic acid, lauric acid, linoleic acid, maleic acid, maleic anhydride, melissic acid, myristic acid, oleic acid, palmitic acid, phosphoric acid, phthalic acid, ricinoleic acid, sebacic acid, stearic acid, succinic acid, 1,2-benzenedicarboxylic acid, and the like, and mixtures thereof. Also suitable are epoxidized oils, glycerol derivatives, paraffin derivatives, sulfonic acid derivatives, and the like, and mixtures thereof with said derivatives.Specific examples of such plasticizers include diethylhexyl adipate, heptylnonyl adipate, diisodecyl adipate, adipic acid polyester, dicapryl adipate, dimethyl azelate, diethylene glycol dibenzoate and dipropylene glycol dibenzoate, polyethylene glycol dibenzoate, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate benzoate, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, methyl (or ethyl or butyl) Phthalyl ethyl glycolate, triethyl citrate, dibutyl fumarate, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, methyl laurate, methyl linoleate, di-n-butyl maleate, tricapryl trimellitate, heptyl nonyl trimellitate, triisodecyl trimellitate, triisononyl trimellitate, isopropyl myristate, butyl oleate, methyl palmitate, tricresyl phosphate, dimethyl phthalate, diethyl phthalate, dibutyl phthalate, diisopropyl phthalate, Butyl phthalate, di-2-ethylhexyl phthalate, octyl decyl phthalate, diisodecyl phthalate, heptyl nonyl phthalate, diundecyl phthalate, ditridecyl phthalate, dicyclohexyl phthalate, diphenyl phthalate, n-butyl benzyl ester of o-phthalic acid, etc., butyl benzyl phthalate, isodecyl benzyl phthalate, alkyl (C7 / C9) benzyl phthalate, dimethoxyethyl phthalate, 7-(2,6,6,8-tetramethyl-4-oxa-3-oxo-nonyl) benzyl Examples of suitable toluene sulfonamides include butyl phthalate, di-2-ethylhexyl sebacate, butyl ricinoleate, dimethyl sebacate, methyl stearate, diethyl succinate, butyl phenyl methyl ester of 1,2-benzenedicarboxylic acid, epoxidized linseed oil, glycerol triacetate, chloroparaffins having about 40% to about 70% Cl, o,p-toluenesulfonamide, N-ethyl p-toluenesulfonamide, N-cyclohexyl p-toluenesulfonamide, sulfonamide-formaldehyde resins, and mixtures thereof.Other suitable plasticizers known to those skilled in the art include castor oil, aromatic petroleum condensates, partially hydrogenated terphenyls, silicone plasticizers such as dimethicone copolyol esters, dimethiconol esters, silicone carboxylates, Guerbet esters, and the like, either alone or in admixture with other plasticizers.

[0030] Additionally, up to about 10% by weight, or about 1-10% by weight, or about 2-7% by weight, or about 2-5% by weight of precipitated calcium carbonate may be added to the TIM composition. Without being bound to any particular theory, it is believed that the optional addition of precipitated calcium carbonate may improve anti-settling of the ATH.

[0031] Additionally, the TIM compositions disclosed herein may optionally further include other suitable additives such as catalysts, stabilizers, adhesion promoters, fillers, colorants, etc. Such optional additives may be present at levels of up to about 10% by weight, or up to about 8% by weight, or up to about 5% by weight, based on the total weight of the TIM composition.

[0032] As demonstrated below by the examples, when placed vertically, the TIM without the silane-terminated urethane prepolymer tends to slip after exposure to weather conditions, but the addition of more than 0.1 wt. % of the silane-terminated urethane prepolymer to the TIM composition solves the slippage problem. Furthermore, it is shown that without the plasticizer, the TIM was too viscous to be of any use.

[0033] Further disclosed herein is a battery pack system in which a cooling unit or plate is coupled to a battery module (formed from one or more battery cells) via the above-described TIM composition, so that heat can be transferred therebetween. In one embodiment, the battery pack system is for use in a battery-powered automobile. The present invention includes the following aspects. Section 1. A thermal interface material composition comprising: a) a non-reactive polyurethane prepolymer that is i) the reaction product of at least one polyisocyanate and at least one hydroxy group-containing compound, and ii) is substantially free of residual isocyanate groups; b) about 70-95% by weight of aluminum trihydroxide; c) about 0.15 to 1.5 weight percent of at least one silane-terminated urethane prepolymer; d) about 1 to 20% by weight of at least one plasticizer; 1. A thermal interface material composition comprising: Section 2. Item 1. The thermal interface material composition of item 1, wherein the non-reactive polyurethane prepolymer is present at a level of about 1 to 25 weight percent, based on the total weight of the composition. Section 3. Item 2. The thermal interface material composition of item 1, wherein the silane-terminated urethane prepolymer is present at a level of about 0.15 to 1.2 weight percent, based on the total weight of the composition. Section 4. 4. The thermal interface material composition of claim 3, wherein the silane-terminated urethane prepolymer is present at a level of about 0.2 to 0.8 weight percent, based on the total weight of the composition. Section 5. Item 2. The thermal interface material composition of item 1, wherein the silane-terminated urethane prepolymer is selected from the reaction product of at least one isocyanate-functionalized silane with one or more polyols, the reaction product of at least one isocyanate-functionalized silane with one or more hydroxyl-terminated prepolymers, and the reaction product of at least one nucleophile-functionalized silane with one or more isocyanate-terminated prepolymers. Section 6. Item 2. The thermal interface material composition of item 1, wherein the silane-terminated urethane prepolymer has a molecular weight in the range of about 200 to 5000. Section 7. Item 7. The thermal interface material composition of item 6, wherein the silane-terminated urethane prepolymer has a molecular weight in the range of about 300 to 3000. Section 8. Item 8. The thermal interface material composition of item 7, wherein the silane-terminated urethane prepolymer has a molecular weight in the range of about 500 to 2000. Section 9. Item 1. An article comprising the thermal interface material composition of item 1. Section 10. Item 10. The article of item 9, further comprising a battery module formed of one or more battery cells and a cooling unit, the battery module being connected to the cooling unit via the thermal interface material composition. EXAMPLES

[0034] material ·HDI - Product name Desmodur TM hexamethylene-1,6-diisocyanate (HDI) obtained from Covestro at H; Monole - C obtained from Dow, Inc. 12 ~C 14 Fatty alcohol initiated fully propoxylated (with propylene oxide) monol (MW 935 g / mol, OH number: 60.4, equivalent weight: 927); · Polyol - polypropylene oxide polyol (functionality: 2, MW: 1000g / mol) obtained from Dow Inc.; Catalyst - Product name DABCO TM dibutyltin dilaurate (DBTDL) obtained from Evonik in T-12; ·STP - Product name Desmoseal TM an aliphatic silane-terminated urethane prepolymer obtained from Covestro under S XP 2636; Plasticizer - Trimethylolpropane trioleate; ATH - aluminum trihydroxide with a bimodal distribution of the average particle size of small particles less than 10 μm and large particles more than 50 μm; Polyester polyol-1 - Product name: Dynacol TM 65°C melting point polyester polyol obtained from Evonik under 7381; Polyesterpolyol-2 - polyester polyol with a melting point of 45°C manufactured by Perstorp; · Polyester urethane prepolymer - reaction product of 4,4'-methylenediphenyl diisocyanate with polyester polyol (polyester polyol-1) in the presence of diisononyl phthalate; · Silane – Vinyltrimethoxysilane.

[0035] Non-reactive polyurethane prepolymer Non-reactive polyurethane prepolymers Pre-1 and Pre-2 were prepared as follows: in a reactor, all ingredients as listed in Table 1 are mixed, except for the catalyst; the reactor is heated to 60°C; the catalyst is added to the mixture; the mixture is stirred at 80°C for 45 minutes under nitrogen atmosphere, then under vacuum for 10 minutes; the colorless reaction product is cooled to room temperature; and the product is transferred to a container. The mass-weighted molecular weight (Mw) and polydispersity index (PDI) of Pre-1 and Pre-2 are measured by gel permeation chromatography (GPC) using Viscotek GPCmax manufactured by Malvern Panalytical.

[0036] [Table 1]

[0037] Comparative Examples CE1 to CE5 and Examples E1 to E7 Sample preparation In each of Comparative Examples CE1-CE5 and Examples E1-E7, all ingredients as listed in Table 2 (liquid ingredients first, then solid ingredients) were added to a planetary mixer or a double asymmetric centrifuge, mixed under vacuum for about 30 minutes, and the resulting TIM (in paste form) was transferred to a cartridge, pail, or drum for storage.

[0038] Thermal Conductivity The thermal conductivity of the resulting TIM paste for each sample was measured using a TIM tester manufactured by ZFW Stuttgart according to ASTM 5470. The measurements were performed in Spaltplus mode at thicknesses of 1.8–1.2 mm, and the absolute thermal conductivity λ (W / m K) was recorded.

[0039] Press-in force The press-in force for the TIM paste in each sample was measured using a tensiometer (Zwick). The TIM paste from each sample was placed on a metal surface. An aluminum piston with a diameter of 40 mm was placed on top of the sample paste and compressed the sample paste to 5 mm (initial thickness). The sample paste was then further compressed to a thickness of 0.3 mm at a rate of 1 mm / s and the force deflection curve was recorded. The force (N) at a thickness of 0.5 mm was recorded as the press-in force.

[0040] viscosity Viscosity was measured by rotational rheology on a rheometer in a plate-plate configuration (25 mm diameter parallel plates) at 23° C. Shear rates were driven from 0.001 to 20 1 / s, with the viscosity reported at 10 1 / s. The initial viscosity was measured immediately after application of the TIM, while the 7-day climate viscosity is the viscosity of the TIM after exposing the TIM to climate conditions for 7 days, where each cycle took 12 hours to complete and consisted of 4 hours at −40° C. (uncontrolled humidity), 4 hours to adjust the temperature to 80° C., and 4 hours at 80° C. with 80% relative humidity by weight.

[0041] Slip test During the sliding test, the TIM in each sample was placed between two substrates (electroplated steel substrate and glass substrate), while the thickness of the compressed TIM was controlled to about 3 mm using a spacer. The sandwich samples were then exposed to climatic conditions in a climate chamber at an angle of 20° for 4 weeks. The samples were then observed for sliding and crack formation.

[0042] As demonstrated herein by E1-E7, with the addition of 0.25 wt% or more of STP, the TIM exhibits no visible cracks and less than 1 mm of slippage. Additionally, as demonstrated by CE4, the absence of plasticizer caused the TIM composition to have too high a viscosity to be of any use.

[0043] [Table 2]

Claims

1. A thermal interface material composition comprising: a) a non-reactive polyurethane prepolymer that is i) the reaction product of at least one polyisocyanate and at least one hydroxy group-containing compound, and ii) is substantially free of residual isocyanate groups; b) 70 to 95% by weight of aluminum trihydroxide; c) 0.15 to 1.5 weight percent of at least one silane-terminated urethane prepolymer; d) 1 to 20% by weight of at least one plasticizer; 1. A thermal interface material composition comprising:

2. The thermal interface material composition of claim 1 , wherein the non-reactive polyurethane prepolymer is present at a level of 1 to 25 weight percent, based on the total weight of the composition.

3. 10. The thermal interface material composition of claim 1, wherein the silane-terminated urethane prepolymer is present at a level of 0.15 to 1.2 weight percent, based on the total weight of the composition.

4. 4. The thermal interface material composition of claim 3, wherein the silane-terminated urethane prepolymer is present at a level of 0.2 to 0.8 weight percent, based on the total weight of the composition.

5. 2. The thermal interface material composition of claim 1, wherein the silane-terminated urethane prepolymer is selected from a reaction product of at least one isocyanate-functionalized silane with one or more polyols, a reaction product of at least one isocyanate-functionalized silane with one or more hydroxyl-terminated prepolymers, and a reaction product of at least one nucleophile-functionalized silane with one or more isocyanate-terminated prepolymers.

6. 10. The thermal interface material composition of claim 1, wherein the silane-terminated urethane prepolymer has a molecular weight in the range of 200 to 5000.

7. 7. The thermal interface material composition of claim 6, wherein the silane-terminated urethane prepolymer has a molecular weight in the range of 300 to 3000.

8. 8. The thermal interface material composition of claim 7, wherein the silane-terminated urethane prepolymer has a molecular weight in the range of 500 to 2000.

9. An article comprising the thermal interface material composition of claim 1.

10. 10. The article of claim 9, further comprising a battery module formed from one or more battery cells and a cooling unit, said battery module being connected to said cooling unit via said thermal interface material composition.

Citation Information

Patent Citations

  • One-component moisture cured polyurethane sealant containing novel water removal agent and preparation method of one-component moisture cured polyurethane sealant

    CN107903865A

  • Heat-conductive resin composition, sheet, and electronic part, semiconductor device, display, and plasma display panel prepared by using the composition

    JP2003313431A

  • Conjugate including heat conductive resin

    JP2013225540A

  • Silane crosslinked compounds

    JP2013534548A

  • Polyurethane resin composition

    JP2015089941A